Detection of Mycobacterium tuberculosis in sputum in patients coinfected with HIV / tuberculosis by various methods (literature review) - I. B. Viktorova; S. Yu. Degtyareva; E. I. Kulabukhova; E. N. Beloborodova; V. N. Zimina (Журнал инфектологии)
The review presents the special aspects of bacillary excretion in  tuberculosis patients co-infected with HIV and the yield of acid-fast  smear depending on the CD4-cell count. Predictors of positive  growth of Mycobacterium tuberculosis from sputum under negative  microscopy in this category of patients are considered. The  experience of different countries of the world on the effectiveness of  various diagnostic algorithms for detecting tuberculosis in HIV/TB  co-infection and the role of molecular-genetic methods in the  diagnosis of tuberculosis are discussed. According to the data  presented in the review, the yield of acid-fast sputum smear  microscopy varies significantly, and depends on a variety of factors,  including the immune status of the patient with HIV infection, the  level of the laboratory service. The different yield of the smear  microscopy in combination with the subclinical course of tuberculosis  and atypical radiologic presentation in patients with HIV infection leads to a delay in diagnosis and to late initiation of  antituberculosis therapy. The culture and the molecular-genetic  methods of sputum examination increase the frequency of detection  of the pathogen, however, the diagnosis of tuberculosis by culture can not be considered rapid in patients with  immunodeficiency. Therefore, in the context of the continuing  increase in the number of patients with co-infection, rapid,  molecular-genetic methods for the detection of MTB DNA should be  included in the algorithm for screening for tuberculosis of HIV- infected patients during their first encounter with the healthcare system.